A computer-driven ventilator liberation protocol in pediatric patients: a single-center pilot randomized controlled trial - Chen, Song; Xiao, Changxue; Lu, Xue; Liao, Min; Liu, Chengjun; Xu, Feng; Li, Jing (Frontiers in Pediatrics, 2025)
ObjectiveTimely liberation from invasive mechanical ventilation (IMV) is important. We aimed to determine the feasibility of our study protocol for the conduction of a larger prospective trial to examine the utility of a computer-driven liberation protocol in pediatric patients.DesignSingle-center pilot randomized controlled trial.SettingSingle, tertiary care, 52-bed, academic pediatric intensive care unit (PICU).PatientsPatients aged from 28 days to 18 years undergoing IMV for more than 24 h.InterventionsPatients were randomly assigned to test and control groups in a ratio of 1:1. The test group underwent ventilator liberation driven by a computerized algorithm combining protocolized screening, air leak testing, and spontaneous breathing testing. The control group underwent ventilator liberation driven by the attending physician according to standard care.Measurements and main resultsA total of 40 patients (20 in each group) were randomized. Baseline characteristics of the two groups were similar. Durations of IMV were 95.3 h (95%CI, 9.07–181.53) in the test group and 113.3 h (95%CI, 85.90–140.70) in the control group and were similar (p = 0.62). PICU length of stay [6.9 days [95%CI, 5.00–8.86] vs. 7.0 days [95%CI, 5.58–8.40]; p = 0.74] and hospital length of stay [22.9 days [95%CI, 11.48–34.24] vs. 26.9 days [95%CI, 17.86–35.94]; p = 0.31] were similar between the test and control groups, respectively.ConclusionsOur pilot study suggests that the conduction of a larger prospective trial of a computer-driven ventilator liberation protocol is feasible in our PICU. And a larger trial is needed to further explore the utility of a computer-driven ventilator liberation protocol.Clinical Trial Registrationhttps://www.chictr.org.cn/showproj.html?proj=168024, Chinese Clinical Trial Registry ChiCTR2200060033.